Pengaruh Profesionalisme Terhadap Intensitas Kerja Karyawan Pada Koperasi Perusahaan Air Minum Tirta Mahakam Kabupaten Kutai Kartanegara - Ilham, Ilham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2017)
The purpose of this research was to know how much the influenced of the Professionalism affect on Employee Work Itensity on Tirta Mahakam Mineral Water Company in Kutai Kartanegara Regency. The study was conducted in September 2016,with  the population data in September 2016 was 10 employees and the number of samples used in this study were 10 employees. The analytical tool used is simple regression analysis and hypothesis testing using t test with SPSS Program. The conclusion in this study that there is a significant influence between Professionalism with Work Itensity Employees at Regional Water Company Cooperative Tirta Mahakam. Thus the hypothesis proposed by researchers in this study are: "Professionalism has a significant effect on Work Itensity Employees at Cooperative Drinking Water Company Regional Tirta Mahakam Kutai Kartanegara Regency" received because proven truth. Keywords: Professionalism, Intensity